Relationship of depersonalization and suicidality in depressed patients - Tošić Golubović, Suzana; Žikić, Olivera; Slavković, Violeta; Nikolić, Gordana; Simonović, Maja (Vojnosanitetski pregled, 2021)
Background/Aim. Depersonalization is considered to be the third leading symptom in psychiatric morbidity. The aim of this study was to investigate the correlation of depersonalization and different patterns of suicidal behaviour in patients suffering from depresssive disorder. Methods. The study included 119 depressed patients divided into two groups: the first group consisted of depressed patients with clinically manifested depersonalization according to the Cambridge Depresonalisation Scale presented score ≥ 70, and the second group consisted of the patients whithout clinically manifested depersonalization symptomatology, or, it was on the subsyndromal level. Subsequently, these two groups were compared regarding the suicidality indicators. Results. According to the Scale for Suicide Ideation of Beck, the depressed patients with depersonalization had statistically significantly higher scores regarding suicidal ideation, both active and passive, more often manifested suicidal desire, suicidal planning and overall suicidality (p
Keywords: depression; depersonalization; suicide; risk factors; mental disorders; behaviour; suicide, attempted.